Microbial fuel cells: A sustainable approach for environmental remediation and green energy generation - Sangili , M H K; Thangavel, K; Alagirisamy, B; Maragatham, S; Pooraniammal, R; Gomathi, V (Plant Science Today, 2026)
Microbial fuel cells (MFCs) are an innovative, eco-friendly bioelectrochemical technology that simultaneously treats wastewater and generates renewable electricity by harnessing the metabolic activity of electroactive microbes. This review surveys advancements in MFC research from 2015 to 2025, highlighting key performance metrics, including power densities that typically range from 100 to 2000 mW/m² and chemical oxygen demand (COD) removal efficiencies between 60 % and 90 % across various organic substrates. MFCs generally consist of an anode chamber, where electrogenic bacteria oxidize organic matter, a cathode chamber that facilitates oxygen reduction and a proton exchange membrane (PEM) separating these compartments. Both pure cultures and mixed microbial communities play vital roles, with electrogenic microbes such as Geobacter sulfurreducens, Shewanella oneidensis and Pseudomonas aeruginosa being particularly important for electricity production. The technology effectively degrades a wide range of pollutants, including heavy metals (HMs), dyes, pharmaceuticals and nutrients, while utilizing waste streams such as domestic wastewater, industrial effluent, agricultural runoff and sludge to generate bioelectricity. Recent advances focus on improving electrode materials, exploring membrane alternatives and optimizing reactor designs to enhance electron transfer efficiency, increase power output and reduce costs. Despite challenges such as low power density, technical complexity, high material costs and scalability limitations, MFCs align with global sustainability goals, particularly the United Nations Sustainable Development Goals (SDGs) 6 and 7, offering potential for decentralized wastewater treatment and clean energy generation. Future research should prioritize interdisciplinary collaboration, policy support and industry engagement to bridge current gaps and advance the commercial deployment of MFC technology.